Prostatic Artery Embolization in the Treatment of Benign Prostatic Hyperplasia: Short and Medium Follow-Up - Rio Tinto, H (2012)
To evaluate the short and mid-term results of prostatic artery embolization in patients with benign prostatic embolization. Retrospective study between March 2009 and June 2011 with 103 patients (mean age 66.8 years, 50-85) that met our inclusion criteria with symptomatic benign prostatic hyperplasia. The clinical outcome was evaluated by the International Prostate Symptom Score (IPSS), quality of life (QoL), International Index of Erectile Function, prostate volume (PV), prostate-specific antigen (PSA), peak urinary flow (Q(max)), and post-void residual volume (PVR) measurements at 3 and 6 months, 1 year, 18 months, and 2 years after PAE and comparison with baseline values was made. Technical and clinical successes, as well as poor clinical outcome definitions, were previously defined. In this review, we evaluate the short and mid-term clinical outcomes and morbidity of patients treated only with non-spherical polyvinyl alcohol. Six months after the procedure, the PV decreased about 23%, IPSS changed to a mean value of 11.95 (almost 50% reduction), the QoL improved slightly more than 2 points, the Q(max) changed to a mean value of 12.63mL/s, the PVR underwent a change of almost half of the baseline value, and the PSA decreased about 2.3ng/mL. In the mid-term follow-up and comparing to the baseline values, we still assisted to a reduction in PV, IPSS, QoL, PVR, and PSA, and an increase in Q(max). Prostatic Artery Embolization is a safe procedure with low morbidity that shows good short- and mid-term clinical outcome in our institution.